Pengaruh Key Audit Matters, independensi, dan objektivitas terhadap Kualitas Audit dengan Kompleksitas Perusahaan sebagai Variabel Moderasi - Melia Putri Hapsari; Nanik Sri Utaminingsih (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2026)
This study examine the effect of Key Audit Matters (KAM), independence, and objectivity on audit quality, with firm complexity serving moderating variable in banking companies during the 2021-2024 period. This study purposive sampling, resulting in 47 banking companies, and analyzed the data using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that KAMs (β=0.249; sig.=0.000) and independence (β=0.104. sig.=0.000) has a positive effect on audit quality. In contrastn objecitivity (β=-0.192; sig.=0.003) has a significant negative impact on audit quality. Corporate complexity moderates the influence of KAM (Sig=0.003) and objectivity (sig.=0.015), but it does not moderate the effect of independence (sig.=0.217) on audit quality. It can be concluded that audit quality is influenced by KAMs, independence, and objectivity, while firm complexity only moderates the relationships between KAMs and audit quality, between objecitivity and audit quality.